Genetics and pathophysiology of mitral valve prolapse - Delwarde, Constance; Capoulade, Romain; Mérot, Jean; Le Scouarnec, Solena; Bouatia-Naji, Nabila; Yu, Mengyao; Huttin, Olivier; Selton-Suty, Christine; Sellal, Jean-Marc; Piriou, Nicolas; Schott, Jean-Jacques; Dina, Christian; et al. (Frontiers in Cardiovascular Medicine, 2023)
Mitral valve prolapse (MVP) is a common condition affecting 2-3% of the general population, and the most complex form of valve pathology, with a complication rate up to 10-15% per year in advanced stages. Complications include mitral regurgitation which can lead to heart failure and atrial fibrillation, but also life-threatening ventricular arrhythmia and cardiovascular death. Sudden death has been recently brought to the forefront of MVP disease, increasing the complexity of management and suggesting that MVP condition is not properly understood. MVP can occur as part of syndromic conditions such as Marfan syndrome, but the most common form is non-syndromic, isolated or familial. Although a specific X-linked form of MVP was initially identified, autosomal dominant inheritance appears to be the primary mode of transmission. MVP can be stratified into myxomatous degeneration (Barlow), fibroelastic deficiency, and Filamin A-related MVP. While FED is still considered a degenerative disease associated with aging, myxomatous MVP and FlnA-MVP are recognized as familial pathologies. Deciphering genetic defects associated to MVP is still a work in progress; although FLNA, DCHS1, and DZIP1 have been identified as causative genes in myxomatous forms of MVP thanks to familial approaches, they explain only a small proportion of MVP. In addition, genome-wide association studies have revealed the important role of common variants in the development of MVP, in agreement with the high prevalence of this condition in the population. Furthermore, a potential genetic link between MVP and ventricular arrhythmia or a specific type of cardiomyopathy is considered. Animal models that allow to advance in the genetic and pathophysiological knowledge of MVP, and in particular those that can be easily manipulated to express a genetic defect identified in humans are detailed. Corroborated by genetic data and animal models, the main pathophysiological pathways of MVP are briefly addressed. Finally, genetic counselling is considered in the context of MVP.